Utility of an Objective Scoring System for Acute Tubular Injury in Renal Allograft Biopsies - Neha Agrawal; Swarnalata Gowrishankar (Indian Journal of Transplantation)
Introduction: Banff criteria define various parameters involved in rejection episodes in renal allografts. However, definite objective criteria to diagnose tubular injury are not well addressed. In the present study, we aim to examine a morphological scoring system for diagnosing and grading acute tubular injury in graft biopsies. Furthermore, we assess the correlation of various morphological features of tubular injury with graft dysfunction at the time of biopsy. Materials and Methods: Fifty renal allograft biopsies with a histological diagnosis of acute tubular injury were selected. The inclusion criteria included absence of rejection, significant interstitial inflammation, infection, or interstitial fibrosis/tubular atrophy >10%. The tubular injury was assessed and scored under five parameters: loss of brush border, presence of lucency, flattening of tubular epithelium, loss of nuclei, and presence of cast or debris. All parameters were scored from 0 to 2 based on objective criteria and assessed in five microscopic fields at ×200. A cumulative score was calculated for each biopsy. A correlation with serum creatinine at the time of biopsy with individual scores and cumulative scores was done. Statistical analysis was done and the Pearson correlation coefficient was obtained. Results: All the individual scores of tubular injury showed a positive correlation with serum creatinine at biopsy, with Pearson correlation coefficient varying from 0.670 to 0.490. The cumulative score for tubular injury also showed a strong positive correlation with serum creatinine, with Pearson correlation = 0.761. Conclusion: An objective semi-quantitative morphological scoring system may help in assessing the extent of tubular injury in graft biopsies, as this correlates well with graft dysfunction.